The significance of volcanic ash in Greenland ice cores during the Common Era. (1st February 2023) - Plunkett, Gill; Sigl, Michael; McConnell, Joseph R.; Pilcher, Jonathan R.; Chellman, Nathan J.
Abstract: Polar ice cores provide long, continuous and well-dated records of past volcanism and have contributed significantly to our understanding of volcanic impacts on climate and society. Sulphate aerosols deposited in the ice are essential for determining the effective radiative forcing potential of past eruptions, but calculations are improved with knowledge of eruption source parameters. Only the co-deposition of volcanic ash can presently confirm the source eruption. Here we review the current state of knowledge regarding the representation of volcanic ash in Common Era ice cores from Greenland and consider what the tephras reveal about the volcanic records in the ice. We augment the published record with a large dataset of previously unreported tephras, the result of a programme of targeted sampling guided by microparticle records that allow us to home in on tephra layers with variable temporal relationships to sulphate aerosol deposition. In addition to revealing the extensive source region of tephra that disperses to Greenland, our review explores for the first time some of the insights provided by the ash about the eruptions, such as the magma type and eruption style. We consider the characteristics of eruptions associated with varying degrees of climate responses and find that the strongest forcing tends to be associated with those producing mafic to intermediate tephra, and that phreatomagmatic processes are commonly involved. The frequent occurrence of multiple eruptions in these instances may also play a role in accentuating the climate response. We note consistencies in the timing of particulate and sulphate aerosol fallout from Icelandic (synchronous) and Alaskan (ash before sulphates) regions, with greater delays (one or more years) for stratospheric transport from tropical eruptions. We outline remaining avenues of research on ice-core tephra that promise to throw light on past volcanic eruption processes, including volatile release and transport, as well as the frequency and impact of small-to-moderate eruptions. We advocate greater integration of wide-ranging tephra research towards a better understanding of volcano-climate relationships. Highlights: More than 50 discrete tephras now known from Common Era Greenland ice cores. Continuous microparticle records enable high-resolution targeted sampling of tephra. Climatically impactful eruptions are mainly associated with mafic-intermediate ash. Microparticle/tephra/sulphate timing provides insights into dispersal pathways.